Florid cemento-osseous dysplasia: a contraindication to orthodontic treatment in compromised areas - Alberto Consolaro; Sergio Rafael Baggio Paschoal; Jose Burgos Ponce; Dario A. Oliveira Miranda
ABSTRACT Florid cemento-osseous dysplasia is a sclerosing disease that affects the mandible, especially the alveolar process, and that is, in most cases, bilateral; however, in some cases it affects up to three or even four quadrants. During the disease, normal bone is replaced with a thinly formed, irregularly distributed tissue peppered with radiolucent areas of soft tissue. Newly formed bone does not seem to invade periodontal space, but, in several images, it is confused with the roots, without, however, compromising pulp vitality or tooth position in the dental arch. There is no replacement resorption, not even when the images suggest dentoalveolar ankylosis. Orthodontists should make an accurate diagnosis when planning treatments, as this disease, when fully established, is one of the extremely rare situations in which orthodontic treatment is contraindicated. This contraindication is due to: (a) procedures such as the installment of mini-implants and mini-plaques, surgical maneuvers to apply traction to unerupted teeth and extractions should be avoided to prevent contamination of the affected bone with bacteria from the oral microbiota; and (b) tooth movement in the areas affected is practically impossible because of bone disorganization in the alveolar process, characterized by high bone density and the resulting cotton-wool appearance. Densely mineralized and disorganized bone is unable to remodel or develop in an organized way in the periodontal ligaments and the alveolar process. Organized bone remodeling is a fundamental phenomenon for tooth movement.